A new model of soft tissue with constraints for interactive surgical simulation. (July 2019) - Hou, Wenguo; Liu, Peter X.; Zheng, Minhua
Highlights: A new FEM based model with constraints is proposed for brain tissue deformation. A new energy function of constraint is introduced into the deformation model. Distance and permanent deformation constraints are introduced. Interactions in the convexity meningioma dissection and hemostasis are properly simulated. The GPU-based implementation achieves high degree of accuracy and computational efficiency. Abstract: Background and objectives: An accurate and real-time model of soft tissue is critical for surgical simulation for which a user interacts haptically and visually with simulated patients. This paper focuses on the real-time deformation model of brain tissue for the interactive surgical simulation, such as neurosurgical simulation. Methods: A new Finite Element Method (FEM) based model with constraints is proposed for the brain tissue in neurosurgical simulation. A new energy function of constraints characterizing the interaction between the virtual instrument and the soft tissue is incorporated into the optimization problem derived from the implicit integration scheme. Distance and permanent deformation constraints are introduced to describe the interaction in the convexity meningioma dissection and hemostasis. The proposed model is particularly suitable for GPU-based computing, making it possible to achieve real-time performance. Results and conclusions: Simulation results show that the simulated soft tissue exhibits the behaviors of adhesion and permanent deformation under the constraints. Experiments show that the proposed model is able to converge to the exact solution of the implicit Euler method after 96 iterations. The proposed model was implemented in the development of a neurosurgical simulator, in which surgical procedures such as dissection of convexity meningioma and hemostasis were simulated.